Reflections on an individualized approach to music literacy in the secondary choral program​. - Seidler, Jessica (Kansas State University, 2020)
In my lesson plan, you will see the unit I have designed to individualize sight singing practice and assessment for each student based on their current music reading level. The way ensembles are set up in my school, I have senior future music majors in the same choir as freshmen who have not taken a music class since 6t​h​ grade general music. As we practiced sight singing as a group at a median level for all students, I realized that the more experienced students were not getting the opportunity to build on their skills and the less experienced students needed additional practice at a more basic level. In this unit, the students’ sight singing levels were evaluated at the beginning of the semester. Students were placed at a level that was comfortable, yet stretched them outside of their comfort zones, with a goal of increasing at least one level per assessment period. They had weekly assignments that were graded on completion, so as not to discourage the growth mindset, but with feedback. Their sight singing was evaluated for accuracy quarterly. The master of music education program at Kansas State University has helped me to enhance my music teaching in many ways. The largest development in my teaching has been in my focus on process over product. In the past, I have sometimes let the desire for a great performance take precedence over taking the time to make sure students understand all the musical concepts in a piece and the reasons for making musical decisions or approaching technique in a certain way. Secondly, I have grown by giving up more control in order to allow students to take ownership of their program. I have done this by giving students more freedom in their musical decisions, literature selection, leadership positions, and community involvement.
Keywords: Music education; Music literacy; Sight-singingChoral music